Gauss-Seidel Method for Calculation of Unbalanced Load Flow. Issue 1 (June 2019) - Nazaruddin; Mahalla; Fauzi
Abstract: Three phase load flow is a study that will provide an overview of the voltage conditions, phase angle, current, power and power losses of each bus in each phase a, b and c. A three-phase load flow study can be used in a three-phase power system control and planning operation. The purpose of this paper is to create a three-phase load flow formulation for unbalanced load conditions. Unbalanced loads on the electric power system will affect consumers, namely a decrease in the voltage received by consumers. Three-phase power flow calculations using the Gauss-Seidel Method (GSM) and computation are done using Matlab software which will be tested on the IEEE 5-bus system. The simulation results show that the unbalanced load flow converges at 32 iterations, the total power on the reference bus (slack bus) is 54.840 MW for phase a, 53.119 MW for phase b, and 64.039 MW for phase c. The IEEE 5-bus system has the largest voltage drop occurring on bus 5 which is 7.7%, 6.9% and 8.9% respectively for phases a, b and c. The biggest power losses occur at line bus 1 to bus 2 at 0.912 MW, 0.854 MW and 1, 228 MW or 2.30%, 2.20% and 2.67% respectively for phases a, b and c.